2021
DOI: 10.1007/s11356-021-15109-5
|View full text |Cite
|
Sign up to set email alerts
|

Genomic markers for the biological responses of Triclosan stressed hatchlings of Labeo rohita

Abstract: Triclosan (TCS) used commonly in pharmaceuticals and personal care products has become the most common pollutant in water. Three days old hatchlings of an indegenous sh, Labeo rohita were given 96h exposure to an environmentally relevant (0.06mg/L) and two moderately lethal concentrations (0.067 and 0.097 mg/L) of TCS and kept for 10 days of recovery for recording transcriptomic alterations in antioxidant/detoxi cation (SOD, GST, CAT, GPx, GR, CYP1a and CYP3a), metabolic (LDH, ALT and AST) and neurological (Ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 93 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…This technique is being used to comprehensively analyze transcriptomic changes and reveal the molecular mechanism caused by TCS toxicity in organisms. Transcriptomics and biochemical research in Labeo rohita indicated that TCS caused liver and kidney damage, abnormal metabolic processes, and digestive system disorders [ 34 , 35 ]. Transcriptome analysis of zebrafish revealed the role of the liver as a target organ for TCS toxicity, with liver steatosis mainly resulting from increased fatty acid synthetase activity, and the uptake and suppression of β-oxidation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This technique is being used to comprehensively analyze transcriptomic changes and reveal the molecular mechanism caused by TCS toxicity in organisms. Transcriptomics and biochemical research in Labeo rohita indicated that TCS caused liver and kidney damage, abnormal metabolic processes, and digestive system disorders [ 34 , 35 ]. Transcriptome analysis of zebrafish revealed the role of the liver as a target organ for TCS toxicity, with liver steatosis mainly resulting from increased fatty acid synthetase activity, and the uptake and suppression of β-oxidation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%